COVID-19 factors and mental health associated with psychological distress level among dentists and dental hygienists in Nepal - Singh, Harender; Chaudhary, Sanjeeb; Thakur, Smriti Narayan; Gupta, Abhishek (Journal of Chitwan Medical College, 2021)
Background: The COVID-19 pandemic, which is caused by a severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), is acknowledged an unprecedented crisis that has adversely affected the population globally and created a situation of emergency in health systems worldwide. The aim of present study was to evaluate the association of COVID-19 factors and psychological factors with psychological distress level among dental professional of Nepal. Methods: The data was collected through a cross-sectional survey conducted online among 350 dental practitioners in Nepal. The data was collected during the period of December 2020 to April, 2021. A self-measuring questionnaire was prepared throgh Google forms to assess COVID-19 factors. In psychological factors category, self-efficacy and subjective overload was measured. General self-efficacy scale was used for the evaluation of self-efficacy and Demand-Scale (short-version) was used for measuring the subjective overload. Kesslers’ K6 scale was used for assessing the distress level among the participants of the study. Multivariate logistic regression was used for statistical analysis. Results: Findings of the study revealed that elevated psychological distress was found more among female dental staff, having fear of contracting COVID-19 from patient, and who have shown higher subjective overload. Lower psychological distress was associated with higher work-experience, and in those who got higher scores for self-efficacy. Conclusions: This study was conducted during the outbreak of deadly infectious coronavirus disease. While exploring the COVID-19 factors and psychological factors on the distress level among dental staff, it is warranted as the effects may be long-term because of their psychological implications on the mental health of dental practitioners.